LAPAROSCOPIC SPLENECTOMY IN ADULT PATIENTS WITH HEMATOLOGICAL DISEASES IN THE GENERAL SURGERY DEPARTMENT OF HOSPITAL NACIONAL DE ITAUGUÁ - Zuarez Román, Natalia Magalí; Yegros Ortiz, Carlos Darío; Montiel Alfonso, Miguel Angel; Barboza Compte, Juan Ignacio (Medicina Clínica y Social, 2022)
Introduction: Splenectomy is a therapeutic option for a variety of hematological pathologies. Laparoscopic surgery has taken advantage and has now become the standard approach in patients undergoing elective splenectomy for hematological pathologies.Objective: To evaluate the most frequent indications, general conditions and intraoperative complications in adult patients with hematological diseases, who underwent laparoscopic splenectomy.Materials and methods: Descriptive, retrospective longitudinal study with non-probabilistic sampling of consecutive cases. Clinical records were reviewed of all patients with splenic pathology who underwent laparoscopic splenectomy with curative intent.Results: The study included 10 patients with a mean age of 47 years. The operation time was 215 60 minutes; the ASA score was 3 ±1; the days of hospitalization were 14 days on average and the estimated blood loss in milliliters was 213 ±366. Seven patients required laparoscopic surgery, four of them ended without complications, while three required conversion to conventional surgery. Accessory spleen was identified in 1 patient. Indications for splenectomy have been idiopathic thrombocytopenic purpura; lymphoproliferative syndromes; felty syndrome; autoimmune hemolytic anemia; and nonautoimmune hemolytic anemia.Discussion: Splenectomy continues to be a useful procedure for numerous hematological pathologies. The need to carry out the corresponding vaccinations and antibiotic prophylaxis must be taken into account, in addition to having the surgical team trained in conventional techniques such as laparoscopic.
Keywords: Splenectomy; spleen; laparoscopy; hematological diseases; surgery.